ChemInform Abstract: Direct S‐Difluoromethylation of Thiols Using the Ruppert—Prakash Reagent. Issue 13 (March 2016) - Prakash, G. K. Surya; Krishnamoorthy, Sankarganesh; Kar, Sayan; Olah, George A.
Abstract: Aromatic and aliphatic difluoromethyl sulfides are selectively obtained with good functional group tolerance from inexpensive and commercially available starting materials.